Spinal Cord Stimulator Electrode Dislodging into the Ligamentum Flavum: A Case Report. Issue 7 (23rd March 2018) - Martin, Aaron J.; Padalia, Devang; Shah, Neal; Singh, Jaspreet; Jassal, Navdeep
Abstract: To date, no case studies specifically reporting an electrode dislodging from its lead wire have been reported. Here we describe a case involving an electrode shearing from the spinal cord stimulator lead, and lodging into the ligamentum flavum during implantation. In this case, an experienced board certified interventional pain management specialist was performing the implantation procedure of a magnetic resonance imaging (MRI) compatible spinal cord stimulator with MR conditional leads. After successful placement of the first lead, the epidural space was accessed via a T11/12 interlaminar approach using loss of resistance technique. When the lead would not advance past the tip of the needle, it was removed in order to reposition the needle slightly. Upon removal of the lead, it was discovered that the first electrode was no longer attached to the wire. Subsequent fluoroscopic imaging revealed that the electrode had lodged within the ligamentum flavum. Upon discussion with the medical director of the device company, it was agreed upon that the electrode should be left in place. The decision was made to proceed with only one lead in place and the remainder of the procedure was completed uneventfully. The patient followed up two weeks later in clinic, and no adverse effect related to the dislodged electrode was reported. The indications and common complications associated with spinal cord stimulation are discussed, followed by factors to consider to help guide decision making in the event of a retained foreign body during a procedure.